Financial literacy and decision making among micro enterprise owners - Bangilan, Mary Joy P.; Dator, Rizabella L.; Gado, Rhue Mae G.; Rafer, Maricar L.; Torres, Aronlyn Laiza F. (b)
Micro enterprises play a vital role in the local economy by providing livelihood opportunities and supporting local economic development (DTI, 2023). However, many micro entrepreneurs are struggling with financial management and decision making due to their limited knowledge and experience. This study assessed the relationship between the financial literacy and decision making among micro enterprises focusing on budgeting, investing, borrowing, taxation and personal financial management. Research utilized quantitative, descriptive, correlational research design, focusing on the 100 micro enterprises owners in San Dionisio Paranaque City, selected through a total population sampling. Data were gathered using a validated self-made questionnaire. Statistical tools such as frequency, percentage, weighted mean, Kruskal-wallis test, and Spearman Rho correlation were used to analyze the data and determine the relationship between financial literacy and decision making. The result revealed that most respondents were engaged in retail businesses, earning 15,000 or below per month, and operating for five years or less. Respondents demonstrated a high level of financial literacy, particularly in budgeting, while taxation has the lowest rating. It was also found that it has strong decision-making skills, especially in cognitive capacity, but limited time and knowledge affected some business choices. Statistical analysis showed no significant differences in financial literacy when grouped according to profile, but a moderate positive correlation between financial literacy and decision-making was found. Moreover, the study concludes that financial literacy significantly influences the decision-making skills of microenterprise owners, with these findings, a Sustainability and Growth Plan was proposed to provide Strong financial knowledge and decision-making ability.
Undergraduate thesis.
Keywords: micro enterprise; financial literacy; decision-making; sustainability; growth plan